International Symposium for Intelligent Transportation and Smart City (ITASC) 2017 Proceedings Branch of ISADS (The International Symposium on Autonomous Decentralized Systems) - Zeng, Xiaoqing; Xie, Xiongyao; Sun, Jian; Ma, Limin; Chen, Yinong (Smart Innovation, Systems and Technologies,, 2017)
This book presents research advances in intelligent transportation and smart cities in detail, mainly focusing on green traffic and urban utility tunnels, presented at the 3rd International Symposium for Intelligent Transportation and Smart City (ITASC) held at Tongji University, Shanghai, on May 19-20, 2017. It discusses a number of hot topics, such as the 2BMW system (Bus, Bike, Metro and Walking), transportation safety and environmental protection, urban utility design and application, as well as the application of BIM (Building Information Modeling) in city design. By connecting the theory and applications of intelligent transportation in smart cities, it enhances traffic efficiency and quality. The book gathers numerous selected papers and lectures, including contributions from respected scholars and the latest engineering advances, to provide guidance to researchers in the field of transportation and urban planning at universities and in related industries. Thefirst conference in the ITASC series started in 2013 as a workshop of The International Symposium on Autonomous Decentralized System (ISADS), held in Mexico City, and the second was held in May 2015, in Tongji University, Shanghai.